Examining the Influence of Large-Scale Hydroelectric Projects on Earth's Rotation, Polarity Shifts, and Magnetic Reversals - Goshu, Belay Sitotaw; Alemu, Yonas Tadesse (Budapest International Research and Critics University, 2025)
The construction of large-scale hydropower projects, such as the Three Gorges Dam, has raised concerns regarding their potential impact on Earth’s rotational dynamics, specifically the axial tilt (obliquity) and its implications for global climate systems. As mass redistribution from these projects could theoretically affect the Earth’s rotation, this study aimed to investigate whether the changes in mass distribution due to the Three Gorges Dam have any measurable effect on the Earth’s axial tilt. This study aimed to evaluate the possible relationship between large-scale hydrological projects and changes in the Earth's rotational characteristics, focusing on obliquity. This was accomplished by combining historical climate records, mathematical models, and satellite-based observational data. Axial tilt measurements from NASA's Earth Orientation Parameters dataset were used to predict and analyze the changes in the moment of inertia caused by the dam's water impoundment. Simulations showed that the Earth's rotational dynamics would only be slightly affected, well below the threshold needed to produce any discernible climatic changes. The study concludes that large-scale hydropower projects, including the Three Gorges Dam, do not have a significant impact on Earth’s axial tilt or long-term climate systems. These findings contribute to the broader understanding of how human-induced changes in mass distribution influence Earth’s rotational dynamics and underscore the resilience of the planet’s natural systems to such interventions.